EXPLORING THE CHALLENGES OF TOMOHON FEMALE ENTREPRENEURS IN BUSINESS ACTIVITIES - Khusna Pelealu; Joy Elly Tulung; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to explore the challenges that faced by Female Entrepreneurs in Tomohon. The qualitative method has used in this research in order to observe and explore the challenges that faced by the Female Entrepreneurs in Tomohon. The Samples of this research are 10 Female Entrepreneurs in Tomohon, whose have a minimum one-year length of run their business, with the age range of 26-64 years old. The result of this research found that the challenges that faced by Female Entrepreneurs in Tomohon are lack of financial, tradition constraints, lack of knowledge and training, gender discrimination of female entrepreneurs, and work-family conflict. There are also other existing challenges based on the experience of the female entrepreneurs in Tomohon, which are competition, employee’s bad behavior, Covid-19 outbreak, the lack of raw material and supply stock, customers’ satisfaction, customers’ debt, and unsafe business environment.